(untitled) (Journal of Economic Research & Business Administration, 2015)
According to variety and diversity of the arisen problems the oil and gas branch of the republic in a generalized view can bepresented in the form of the big system functioning as in the internal and in environment where the internal environment is a domestic market of the state and external, taking into account economy globalization-is a world market.In the conditions of integration of economy into the world economy there is an influence of environment on internal, the internal environment on oil and gas system of the republic and vice versa.